(3MeGjI GdeSJgdc GdEdcJQhfj (B:s (3aj VhA bGfhf MeGjI GdeSJgdc GdeUQj hGdJhLjgGJ GdChQHjI hGdbGfhf GdaQfSj hbGfhf GdjhfjSJQGd GdfehPLj ddJLGQI GdEdcJQhfjI eYdbG YdjgG HCMOK CMcGe eMceI GdfbV GdeUQjI hGdaQfSjI hGdeMGce GdGbJUGOjI (B/s - (3NGdO, chKQ SYjO YOfGfs; (3GdbdjhHj, SejMI eUWais ((3GdEScfOQjI, eUQ (B:s (3OGQ GdLGeYI GdLOjOI,s, 2016)
(3jJfGhd gPG GdcJGH ehVhY MeGjI GdeSJgdc GdEdcJQhfi hgh GdTNU GdPi jJYGbO ef NdGd CMO GdhSGFd GdEdcJQhfjI GdMOjKI eKd GdEfJQfJ(B. (3hjTed GdcJGH OQGSI ebGQfI dYOO ef GdJhLjgGJ GdChQhHjI hGdJTQjYGJ GdaQfSjI hGdeUQjI ceG JTJed GdcJGH Ydi YOO ef GdCMcGe GdbVGFjI GdUGOQI ef eMceI GdYOd GdChQhHjI hGdCMcGe GdUGOQI ef GdeMGce GdaQfSjI hGdCMcGe GdUGOQI ef GdeMGce GdGbJUGOjI GdeUQjI hGdCMcGe GdUGOQI ef eMGce GdLfM bHd CfTGA GdeMGce GdGbJUGOjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B696-699.s
Keywords: (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs; (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs